1966
DOI: 10.1111/j.1751-1097.1966.tb05823.x
|View full text |Cite
|
Sign up to set email alerts
|

SKIN‐PHOTOSENSITIZING FUROCOUMARINS: PHOTOCHEMICAL INTERACTION BETWEEN DNA AND —O14CH3 BERGAPTEN (5‐METHOXY‐PSORALEN)

Abstract: For some years the mechanism of the photosensitizing effects displayed by some furocoumarins on various biological substrates (human and guinea-pig skin, bacteria cultures, mammalian cells adapted to in vitro growth, viruses) have been studied. Recently it has been pointed out that a photoreaction occurs between the photosensitizing furocoumarins and DNA after irradiation at 3655 A. By use of a labeled furocoumarin, i.e.-O"CH, bergapten or 5-methoxy-psoralen, this has been confirmed and more extensively studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

1971
1971
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(21 citation statements)
references
References 14 publications
2
19
0
Order By: Relevance
“…The photochemistry of furocoumarins (psoralens) has received considerable attention from several groups of workers (2,10,11,19). The parent compound, psoralen, and some of its derivatives have a photosensitizing action on viruses (3,12), bacterial cells, and mammalian cultures (2,13) and produce lethal and mutagenic effects.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The photochemistry of furocoumarins (psoralens) has received considerable attention from several groups of workers (2,10,11,19). The parent compound, psoralen, and some of its derivatives have a photosensitizing action on viruses (3,12), bacterial cells, and mammalian cultures (2,13) and produce lethal and mutagenic effects.…”
Section: Methodsmentioning
confidence: 99%
“…The in vitro specificity of activated mitomycin C for double-stranded DNA has been established; however, it reacts nearly as well with RNA (24). In contrast, psoralens, upon irradiation with 360 nm light, bind primarily to native DNA (11,14). Also, the products formed by irradiation of psoralen with the DNA components, thymine and cytosine, have been isolated and characterized ( Fig.…”
mentioning
confidence: 99%
“…Psoralen and other furocoumarins photoreact with pyrimidine bases of DNA, bot in vitro and in vivo [1][2][3][4][5][6][7][8], under irradiation at long wavelength ultraviolet light. A C4-cycloaddition to the 5,6-double bond of pyrimidine bases occurs: furocoumarins can photoreact either with their 3,4-or 4',5'-double bond, forming therefore two types of photoadducts.…”
Section: Introductionmentioning
confidence: 99%
“…They are also used to increase the tolerance of human skin to solar radiation (Fitzpatrick, Arndt, E1 Mofty and Pathak 1966, Imbrie, Daniels, Bergeron, Hopkins and Fitzpatrick 1959, and El Mofty 1968. Musajo, Rodighiero, Breccia, Dal'Acqua and Malesani (1966), Musajo and Rodighiero (1970) and Pathak and Kramer (1969) have shown that 4,5',8-trimethylpsoralen (trisoralen, trixsalen) form a stable C4-cycloaddition product to DNA in aqueous solutions as well as in epidermal cells after longwavelength ultra-violet irradiation. Experiments reported in this study were designed to determine how this trisoralen photoproduct on the DNA molecule might lead to the many biological manifestations of furocoumarin photosensitization.…”
Section: Introductionmentioning
confidence: 99%